Ultra-wideband power amplifier design for large signal application / Ragavan Krishnamoorthy - Ragavan , Krishnamoorthy (2020)

(untitled)
Broadband power amplifier design has become one of the most critical enabling block in today’s wireless communication technology. Numerous research efforts have been carried out throughout the years to establish high efficiency over wideband RF transmitter. This research work presents two approaches in achieving ultra-broadband power amplifier for RF transmitter. Firstly, a new technique for the design of ultra-broadband RF power amplifier is introduced, in which a combination of the reactance compensation and third-harmonic tuning are adopted. The design goal is to achieve 40 dBm (10W) output power across a wide frequency bandwidth operation. Theoretical design equations were developed to enable a designer to replicate the amplifier in the need of a highlighted specifications. The experimental result shows high efficiency achievement, more than 60%, throughout a wide bandwidth between 0.4 - 2.0 GHz. Another new design technique for broadband RF power amplifier is introduced for second approach, with combination of large signal X-parameter and Real-Frequency Technique (RFT). A theoretical analysis of large signal X-parameter is revisited, and a simplification method is introduced to determine the optimum large signal impedances of GaN HEMT device in use. With the optimum impedance extraction over the wide frequency range (0.3 - 2.0 GHz), a wideband matching network is constructed employing RFT and the final design is implemented with practical mixed-lumped elements. The prototype broadband RF PA demonstrates an output power of 40 dBm (10 W). The average drain efficiency of the PA is found to be more than 60% over the frequency band of (0.3- 2.0 GHz). These techniques demonstrated small size area and lower cost implementation which are suitable for RF communications applications.